Ideal Bose-gas in nonadditive statistics - Rovenchak, A. (Физика низких температур, 2018)
The paper analyzes an approach to the generalization of the conventional Bose–Einstein statistics based
on the nonadditive entropy of Tsallis. A detailed derivation of thermodynamic functions is presented. The calculations are made for the specific heat of two model systems, namely, the ideal three-dimensional gas obeying
the nonadditive modification of the Bose–Einstein statistics and the system with linear excitation spectrum attempted as a qualitative approximation of liquid ⁴He thermodynamics. Проаналізовано підхід до узагальнення традиційної статистики Бозе–Ейнштейна на основі неадитивної ентропії Цалліса. Подано докладне виведення термодинамічних функцій.
Зроблено розрахунки для питомої теплоємності двох модельних систем, а саме: ідеального тривимірного газу, що підкоряється неаддитивній модифікації статистики Бозе–Ейнштейна,
та системи з лінійним спектром елементарних збуджень,
прийнятої за якісне наближення термодинаміки рідкого ⁴He. Проанализирован подход к обобщению традициионной
статистики Бозе–Эйнштейна на основе неаддитивной энтропии Цаллиса. Представлен подробный вывод термодинамических функций. Сделаны расчеты для удельной теплоемкости
двух модельных систем, а именно: идеального трехмерного
газа, подчиняющегося неаддитивной модификации статистики Бозе–Эйнштейна, и системы с линейным спектром элементарных возбуждений, принятой как качественное приближение термодинамики жидкого ⁴He.